Using GitHub Classroom To Teach Statistics. Issue 2 (4th May 2019) - Fiksel, Jacob; Jager, Leah R.; Hardin, Johanna S.; Taub, Margaret A.
Abstract: Git and GitHub are common tools for keeping track of multiple versions of data analytic content, which allow for more than one person to simultaneously work on a project. GitHub Classroom aims to provide a way for students to work on and submit their assignments via Git and GitHub, giving teachers an opportunity to facilitate the integration of these version control tools into their undergraduate statistics courses. In the Fall 2017 semester, we implemented GitHub Classroom in two educational settings—an introductory computational statistics lab and a more advanced computational statistics course. We found many educational benefits of implementing GitHub Classroom, such as easily providing coding feedback during assignments and making students more confident in their ability to collaborate and use version control tools for future data science work. To encourage and ease the transition into using GitHub Classroom, we provide free and publicly available resources—both for students to begin using Git/GitHub and for teachers to use GitHub Classroom for their own courses.